2013
DOI: 10.1111/jace.12525
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Light Absorption Processes in Transparent Polycrystalline MgAl2O4 and YAG

Abstract: Parasitic radiation absorption by impurities located in transparent polycrystalline ceramic hosts may significantly impair their functioning. At least two classes of impurity which can act as parasitic absorbers were encountered: transition or rareearth metal cations and neutral species (molecules or atoms) trapped in lattice void spaces. The most ubiquitous parasitic absorbers, able to affect transmission in the visible domain, have been identified for the case of MgAl 2 O 4 -spinel and Y 3 Al 5 O 12 -garnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
2
22
1
Order By: Relevance
“…In the case of carbon, since the single atoms or atom clusters absorb the light at all the visible range without showing any local absorption bands, the T in spectra exhibit featureless curves; the T in value monotonously increases with increasing k. The T in spectra of the SPSed spinels [14][15][16] also showed the featureless T in spectrum curves. If this is also the case for the present material, DT in,(PH-AR) % 10% at k > 400 nm can be mainly ascribed to the parasitic light absorption caused by the glassy carbon, such as non-crystalline carbon atoms and/or atom clusters [78].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the case of carbon, since the single atoms or atom clusters absorb the light at all the visible range without showing any local absorption bands, the T in spectra exhibit featureless curves; the T in value monotonously increases with increasing k. The T in spectra of the SPSed spinels [14][15][16] also showed the featureless T in spectrum curves. If this is also the case for the present material, DT in,(PH-AR) % 10% at k > 400 nm can be mainly ascribed to the parasitic light absorption caused by the glassy carbon, such as non-crystalline carbon atoms and/or atom clusters [78].…”
Section: Discussionsupporting
confidence: 54%
“…Goldstein et al [78] suggested that both single carbon atoms and/or carbon atom clusters become a light absorber for transparent spinel. The absorption caused by impurities has generally been defined as the parasitic light absorption in order to distinguish from those of point defects (vacancies).…”
Section: Discussionmentioning
confidence: 99%
“…However, if individual carbon atoms exist within the grains, they create absorption bands in the transparent spectrum due to the formation of point defects. 31) This is not the case in the present study because the spectrum monotonously changed with the wavelength of the incident light.…”
Section: /Spcontrasting
confidence: 53%
“…Certain intrinsic and extrinsic point defects [like host lattice ion vacancies or interstitials, transition‐metal or rare‐earth cations (TM + or RE + ), OH − anions, individual (or small clusters) of absorber, neutral atoms, or molecules (e.g., C 0 , S 8 )] are able to selectively absorb and/or emit various (usually narrow) portions of the spectrum domain for which the TCs discussed here are supposed to be transparent (0.1–15 μm) . Some of these absorber/emitter units are undesired impurities, while others are dopants added on purpose; the latter confer new functionalities to passive hosts, leading to applications for TCs in areas like lasers, phosphors, scintillators, filters, etc.…”
Section: Light Transmitting Ceramics’ Appeal Market and History Phmentioning
confidence: 99%
“…Part of the EMR which is expected to transit through the TC is absorbed by dopants, e.g., in fluorescent parts, or by various impurities, impairing (sometimes dramatically) the functionality of the host. As a first step in reducing such adverse effects, it is important to identify all potentially negative agents as, for example, the detection of carbon inside hot‐pressed or HIPed parts . During HIP at 200 MPa, carbon diffused into the parts even without any open porosity and at starting (before HIP) bulk densities of 97%–99% TD; this phenomenon occurs frequently at over 1500°C and is quasi‐absent below 1400°C.…”
Section: Progress In Tcs Understanding and Engineeringmentioning
confidence: 99%